2012
DOI: 10.1371/journal.pgen.1002875
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Genome-Wide Transcriptional Responses of the Filamentous Fungus Aspergillus niger to Lignocellulose Using RNA Sequencing

Abstract: A key challenge in the production of second generation biofuels is the conversion of lignocellulosic substrates into fermentable sugars. Enzymes, particularly those from fungi, are a central part of this process, and many have been isolated and characterised. However, relatively little is known of how fungi respond to lignocellulose and produce the enzymes necessary for dis-assembly of plant biomass. We studied the physiological response of the fungus Aspergillus niger when exposed to wheat straw as a model li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(228 citation statements)
references
References 64 publications
(67 reference statements)
11
215
0
2
Order By: Relevance
“…The q-RT-PCR analysis of the expression of a 15-gene set confirmed that the results from the RNA-Seq analysis provided a reliable representation of gene expression. Furthermore, the use of the genome of a closely related species as the reference in an RNA-Seq analysis was recently validated (33,34). We also noted that the percentage of reads that mapped to the reference was similar to the values obtained by other groups in their RNA-Seq analyses of the fungus Phanerochaete carnosa (54) and the yeast Scheffersomyces stipitis (55), with 63% and 71%, respectively, compared to our finding of 57% here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The q-RT-PCR analysis of the expression of a 15-gene set confirmed that the results from the RNA-Seq analysis provided a reliable representation of gene expression. Furthermore, the use of the genome of a closely related species as the reference in an RNA-Seq analysis was recently validated (33,34). We also noted that the percentage of reads that mapped to the reference was similar to the values obtained by other groups in their RNA-Seq analyses of the fungus Phanerochaete carnosa (54) and the yeast Scheffersomyces stipitis (55), with 63% and 71%, respectively, compared to our finding of 57% here.…”
Section: Discussionsupporting
confidence: 89%
“…All the nonmapped reads were considered to originate from P. coccineus and were used for the differential expression analysis. As the genome from P. coccineus was not available, the libraries were mapped against the predicted transcripts from Trametes versicolor (version 1.0 [28]), a species very closely related phylogenetically (32)(33)(34). The Qseq parameters were set to the default, and read counts were normalized via RPKM (reads per kilobase of exon model per million mapped reads).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the A. oryzae targeted the hemicellulose (xylan) for degradation first, possibly due to its lower recalcitrance compared to that of crystalline cellulose or lignin. This is similar to the pattern (expression sequence of CAZy genes) seen by Delmas et al [31], who used next-generation RNA sequencing technology (RNA-seq) in a study with A. niger cultured on wheat straw. It seems that in the absence of a preferred carbon source (glucose or starch), both A. oryzae and A. niger preferentially degrade hemicelluloses, perhaps as a pre-requisite of breaking down the lignocellulosic structure.…”
Section: Cbp Using a Niger With Either S Cerevisiae Ncyc2592 Or Ncysupporting
confidence: 82%
“…Various enzymes from the CAZy database (http://www.cazy.org/) of carbohydrate degradation specific enzymes are indicated as being potentially involved in the successful degradation of lignocellulosic substrates such as BSG, many of which come from fungal enzymatic systems such as brown and white rot fungi (Evans et al, 1994;Delmas et al, 2012). These enzymes include members of the glycoside hydrolase (GH) family, carbohydrate esterase (CE) family, and polysaccharide lyase (PL) family (Fig.…”
Section: Introductionmentioning
confidence: 99%